The Effects of Ubiquinone on the Antioxidant System in Male Rats Exposed to Saccharin-Induced the Hepatic Toxicity - Aboukhezam, Barga; Ahmed, F. A. (Journal of Pure & Applied Sciences, 2024)
Saccharin (Sac) is a widely used artificial sweetener with significant applications in the food industry, pharmaceutical formulations, and tobacco products. Despite its popularity, saccharin has drawn attention due to its potential carcinogenic effects and associations with various health risks, including renal impairment, hepatic dysfunction, obesity, and diabetes. This study aimed to investigate the protective effects of Ubiquinone, or coenzyme Q10 (COQ10), on liver toxicity induced by saccharin, focusing on oxidative stress and antioxidant markers. In this experiment, rats were divided into six groups of ten. The control group received no treatment, while the second group was administered COQ10 at a dosage of 20 mg per kilogram of body weight. The third and fourth groups were given saccharin at 1/10 and 1/20 of the lethal dose 50 (LD50), respectively. The fifth and sixth groups received saccharin at the same dosages as the third and fourth groups, but with additional COQ10 supplementation. All treatments were administered orally for 30 days, after which liver tissues were collected to assess oxidative stress and antioxidant markers. The results revealed that saccharin significantly increased oxidative stress in the liver, as evidenced by elevated levels of malondialdehyde (MDA) and oxidized glutathione (GSSG). Additionally, saccharin-treated groups exhibited a marked decrease in antioxidant markers, including reduced glutathione (GSH) and superoxide dismutase (SOD). However, the groups that received COQ10 alongside saccharin showed significant improvement, with oxidative stress and antioxidant levels nearly returning to those observed in the control group. These findings suggest that saccharin consumption promotes the generation of reactive oxygen species and contributes to liver damage, characterized by necrotic hepatocytes, sinusoidal dilatation, and inflammatory infiltration. The protective effects of COQ10 in mitigating saccharin-induced oxidative stress highlight its potential as a therapeutic agent for preventing liver damage associated with saccharin intake.